Customer Integration in Innovation Development: Illuminating Different Design Aspects - Hanker, Anna-Lena; Justus Liebig University Giessen (My University, 2021)
The aim of integrating customers into innovation development is to create innovations for improved market acceptance as customer integration enables a better understanding of customer needs, which strengthens a firm’s competitive advantage in the respective market. This dissertation provides an up-to-date overview of customer integration in innovation development and reveals existing research gaps with corresponding future research questions. Additionally, some of the most prominent research gaps regarding different customer integration design aspects in innovation development are addressed. Consequently, this dissertation advances theoretical and practical perspectives on customer integration in innovation development as an important facet of external knowledge integration within the open innovation paradigm.
Keywords: Customer Integration; Innovation Development; Open Innovation; Psychologial Ownership; Idea Contest Design; Value Co-Creation; ddc:650